Effect of stocking density on the growth performance of red tilapia and water quality in zeolite supplemented closed system - Ku Boon Hong (2019)
Increasing in fish density in the culture systems increases the fish production; however the intensification in cage culture system resulted in massive mortality in fish. The main objective of this study is to determine the effect of stocking density, (5, 10, 15, 20, and 25 fry/aquarium) on water quality and growth parameters of fresh water aquarium fish, red tilapia, Oreochromis niloticus, at different stocking density supplemented with zeolite. This study also aimed to compare the water quality and growth performance of fish in treatments with and without zeolite. Red tilapia fry (12.90±0.01 g, 81.95±0.02 cm) were stocked into aquarium (40×20×20 cm). Five treatments (containing zeolite) with two replicates and one replicate (without zeolite) were used: T1 - 5, T2 - 10, T3 - 15, T4 - 20, and T5 - 25 fry/aquarium. Fish were fed twice a day with 2% of total biomass. The water quality parameters of each aquarium were monitored by using YSI model 556 multi-parameter and UV-VIS spectrophotometer. Weight and length of red tilapia was measured every two weeks by using electronic balance and vernier calipers. After 9 weeks, the zeolite treatments which recorded the highest final mean weight was T1 (40.27±15.87) while in T5 (17.26±0.15) lowest mean weight was recorded. Specific growth rate and length gain in T1 (1.74%, 24.38 mm) was significantly (p<0.05) higher than other treatments. Based on the water quality recorded, significant differences (p<0.05) were found in all water quality parameters among treatments except salinity. On the other hand, there was no significant difference (p>0.05) in growth parameters between the treatments with and without zeolite. The water quality recorded in zeolite supplemented treatments was better than in control. The findings of this paper will be useful for the practitioners to understand the best practice for stocking density in zeolite supplemented closed system.